RP-HPLC Method Development And Validation For Simultaneous Estimation Of Sulbactam And Cefoperazone In Dosage Form And In Plasma - K.VINOD KUMAR; J.DHARUMAN; A. KARUNA SREE (International Journal of Pharma and Bio Sciences, 2010)
A simple, precise and accurate RP-HPLC method has been developed for the simultaneous estimation of sulbactam and cefoperazone in dosage form and in plasma using ornidazole as an internal standard. The chromatographic separation was achieved on a phenomenex phenyl hexyl column (250mmX4.6mm,5µm) using a gradient system with mobile phase composed of acetonitrilephosphate buffer(sodium phosphate-20mM)(65:35v/v)pH 3.5 adjusted with orthophosphoric acid at a flow rate of 1 ml/min and detector wavelength190nm.The retention time of sulbactam and cefoperazone was 3.1 and 4.1.The validation of the proposed method was carried out for specificity, linearity, accuracy, precision, robustness and limit of detection and quantitation.The linear dynamic ranges were from 10-50µg/ml for sulbactam and 10-50µg/ml for cefoperazone.Limit of detection and quantitation for sulbactam were 50ng/ml and 300ng/ml for cefoperazone were 50ng/ml and 400ng/ml respectively. The developed method can be used for routine quality control analysis of titled drugs in combination in formulation and in plasma.